PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU PENYEBARAN PROMOSI INVESTASI MENYESATKAN PADA PLATFORM BINARY OPTION DALAM PERSPEKTIF UU ITE NO. 19 TAHUN 2016 - Ramadhana, Widodo; Chew, Andrew; Irwanda, Irwanda (Penerbit Lafadz Jaya, 2023)
Many people are tempted to take part in trading due to the presence of affiliates, influencers or public figures in promoting Binomo as an investment platform. For this reason, it is necessary to study the forms of misleading investment promotion and the criminal responsibility of perpetrators who promote misleading investment products on the binary options platform. The type of research is normative law. The nature of research is descriptive analysis. Data collection techniques use library searches. Data analysis was carried out qualitatively. A misleading form of investment promotion is carried out by showing the profits obtained along with the luxuries resulting from trading to attract target customers. This violates the provisions of Article 10 UUPK and Article 28 paragraph (1) UU ITE which states: